2021
DOI: 10.33533/jpm.v15i2.3193
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Upper Arm Circumference vs Body Mass Index in Association with Blood Pressure in Young Men: A Cross-Sectional Study

Abstract: Hypertension and obesity are major risks factor for cardiovascular disease (CVD), which is one of the leading causes of mortality. Many studies have shown that body mass index (BMI) and mid-upper arm circumference (MUAC) measurements are associated with blood pressure in children and adults. However, the association has not been studied extensively in young men. This study aims to investigate the correlation between BMI with blood pressure and MUAC and MUAC with blood pressure in young men. This is a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These findings are consistent with previously published studies [16]. Our results are not consistent with the study which show no significant correlation of SBP, DBP with MUAC [24]. The inconsistency might be since other study has used only small sample size.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with previously published studies [16]. Our results are not consistent with the study which show no significant correlation of SBP, DBP with MUAC [24]. The inconsistency might be since other study has used only small sample size.…”
Section: Discussionsupporting
confidence: 83%
“…Further, our study showed that DIABPD had a statistically signi cant correlation with arm circumference, whereas the previous studies had not addressed it. The possible explanation is that MUAC represents higher muscle mass in men and adiposity in women (33).…”
Section: Discussionmentioning
confidence: 99%